O Brasil e Rondônia no censo demográfico 2022: apontamentos iniciais - Ricardo Gilson da Costa Silva (Confins)
The text analyzes the partial results of the 2022 Demographic Census, to indicate some spatial transformations applied to two territorial units: Brazil and the state of Rondônia. As a method, the resources of Excel software were used to perform calculations of relative and absolute population variation, and Philcarto to produce maps. The results showed that the growth of the Brazilian population varied according to the regions and states of the federation, with emphasis on the South, North and Midwest. As for the state of Rondônia, it was the only one in the North region to obtain a rate lower than the national and regional average, whose performance impacted most of the municipalities that make up this federation unit.